HEART RATE VARIABILITY ANALYSIS AT ARRHYTHMIA WITH SAVED SINUS RHYTHM: PHYSIOLOGICAL APPROACH FOR CLUSTERISATION - Martynenkо, A.V.; Yabluchansky, M.I.; Ostropolec, S.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The method extending spectral analysis of heart rate variability (HRV) application for patients with sinus arrhythmia was proposed. The method is based on rhythmogram physiological clusterization that generalized as empirical smooth of time series. Рroposed method exactly split mixed signal on true independent sources: we obtain stochastic and harmonic sources when we split real HRV records and TP of harmonic source good correlated with expected TP value for patients’ age group. Thus method extends HRV technology for medical practice.